Implementasi pembentukan akhlak perspektif Al-Ghazali di MA Assalam Grobogan - Arrizky, Muhammad Naufal; Afifi, Zaki (Program Studi Magister Pendidikan Agama Islam, 2026)
The issue of adolescent morality highlights the urgency of strengthening education that not only emphasizes cognitive aspects, but also the internalization of values and behavioral habits. Al-Ghazali's thoughts on the formation of morality, which integrate knowledge, appreciation, and practice, are relevant to be analyzed within the framework of Bloom's Taxonomy, which covers the cognitive, affective, and psychomotor domains. This study aims to analyze the implementation of character building at MA Assalam Grobogan based on Al-Ghazali's perspective within the framework of these three domains of learning outcomes. The research uses a descriptive qualitative approach with a phenomenological perspective. Data were collected through interviews, observations, and documentation, then analyzed through the stages of data condensation, data presentation, and conclusion drawing while maintaining validity through triangulation and member checks. The results show that character building has covered all learning outcome domains, namely the cognitive domain through lectures, discussions, presentation of arguments, and memorization; the affective domain through exemplary behavior, advice, and the targhib wa tarhib approach; and the psychomotor domain through routine habits, continuous practice, and a point-based reward and punishment system. This implementation is in line with Al-Ghazali's concept of moral education and Bloom's Taxonomy framework, although this study has not measured the long-term effectiveness of moral character formation in students. Abstrak Permasalahan akhlak remaja menunjukkan urgensi penguatan pendidikan yang tidak hanya menekankan aspek kognitif, tetapi juga internalisasi nilai dan pembiasaan perilaku. Pemikiran Al-Ghazali tentang pembentukan akhlak yang mengintegrasikan ilmu, penghayatan, dan pengamalan relevan dianalisis dalam kerangka Taksonomi Bloom yang meliputi ranah kognitif, afektif, dan psikomotorik. Penelitian ini bertujuan menganalisis implementasi pembentukan akhlak di MA Assalam Grobogan berdasarkan perspektif Al-Ghazali dalam kerangka tiga domain hasil belajar tersebut. Penelitian menggunakan pendekatan kualitatif deskriptif dengan perspektif fenomenologis. Data dikumpulkan melalui wawancara, observasi, dan dokumentasi, kemudian dianalisis melalui tahapan kondensasi data, penyajian data, dan penarikan kesimpulan dengan menjaga keabsahan melalui triangulasi dan member check. Hasil penelitian menunjukkan bahwa pembentukan akhlak telah mencakup seluruh domain hasil belajar, yakni ranah kognitif melalui ceramah, diskusi, penyajian dalil, dan hafalan; ranah afektif melalui keteladanan, nasihat, dan pendekatan targhib wa tarhib; serta ranah psikomotorik melalui pembiasaan rutin, latihan berkelanjutan, serta sistem ganjaran dan hukuman berbasis poin. Implementasi ini selaras dengan konsep pendidikan akhlak Al-Ghazali dan kerangka Taksonomi Bloom, meskipun penelitian ini belum mengukur efektivitas jangka panjang pembentukan akhlak peserta didik.